Convective-cum-Microwave Drying Characteristics of Ginger (Zingiber officinale) - Sunanda; Kumar, Satish; Ramya, H. G.; Alam, M. S.; Gautam, Rakesh B. (International Journal of Bio-resource and Stress Management, 2023)
Investigations were carried out to study the effect of drying parameters viz. exposure time, pause time and power level on convective-cum-microwave drying of ginger. Multilayer drying of ginger was carried out at 3 levels each of exposure time (5-25s), pause time (10-100s) and microwave power levels (270–1350W). Drying air temperature, relative humidity, air velocity, moisture content, moisture ratio and drying rate were measured. Quality attributes included rehydration ratio, shrinkage ratio, colour change, oil content and overall acceptability. Multilayer drying of ginger with an initial moisture content of 89% wb was carried out at 60 °C, air velocity of 3.5 m/s and loading density of 44.66 kg/m2 in a mechanical drier till the moisture content reached 35% (wb) followed by drying in microwave oven to a final moisture content of 6% (db). The drying rateincreased with the increase in exposure time and power level whereas it decreased with the increase in pause times. The increase in exposure time resulted in increased rehydration ratio, colour change and decrease in shrinkage ratio, oil content and overall acceptability. Pause time had little effect on quality parameters. The increase in power level resulted in increase in rehydration ratio, colour change and decrease in shrinkage ratio, oil content and overall acceptability. The optimum conditions were found to be 8.6s exposure time, 55s pause time and 810W power level. During storage the maximum variation in quality was observed in LDPE package and the results were comparable for HDPE and Laminate packages.